Analysis of Metaheuristic Solutions to the Response Time Variability Problem - Joshi, Rajendra Prasad (Api Journal of Science, 2024)
The problem of variation in the response time is known as response time variability problem (RTVP). It is combinatorial NP-hard problem which has a broad range of real-life applications. The RTVP arises whenever events, jobs, clients or products need to be sequenced so as to minimize the variability of the time they wait for their next turn in obtaining the resources they need to advance. In RTVP the concern is to find out near optimal sequence of jobs with objective of minimizing the response time variability. The metaheuristic approaches to solve the RTVP are: Multi-start (MS), Greedy Randomized Adaptive Search Procedure (GRASP) and Particle Swarm Optimization (PSO). In this paper, the computational result of MS and GRASP will be analyzed.